Strength-based strategies and assets that Black and Latina/o middle and high school students use to navigate contextual barriers of math engagement - Hsieh, Ta-Yang; Yu, Mark Vincent B.; Holquist, Samantha E.; Scott, Alyssa; Crowder, Marisa K.; Kelley, Claire G. E.; Reyes, Olivia; , Adapted Measure of Math Engagement Research Group; Chavira, Antonio; Espy, Brianna; Ombongi, Ryan; Ssemukutu, Serrah; et al. (Frontiers in Education, 2025)
BackgroundRacial disparities in math remain a critical issue in the United States. For example, the U.S. educational system often fails to recognize or uplift the funds of knowledge and other cultural assets that Black and Latina/o students possess, which has implications for their engagement in math. The goal of this study is to understand, from the perspectives of Black and Latina/o students, what are the salient barriers for math engagement. Importantly, aligned with our strength orientation, we also aim to understand what assets-based strategies Black and Latina/o students use to navigate the barriers.ResultsBlack and Latina/o students (n = 107) reported barriers to math engagement that span across the micro- (e.g., classroom management and structure), exo- (e.g., distractions from personal technology use), macro- (e.g., math stereotypes and misconceptions), and chrono-system (effects of COVID). To navigate those barriers, Black and Latina/o students identified various assets, such as study strategies, interactive instruction, good use of technology, peer support and collaborative learning, teacher support, positive teacher-student relationships, and family support and capital.ConclusionIn presenting both the barriers Black and Latina/o students face for their math engagement, as well as the strength-based strategies they utilize to navigate such barriers, we present a holistic view of math engagement that centers the role of culture and contexts. Overall, our findings contribute to a more humanizing way to understand the educational inequities that Black and Latina/o students navigate in STEM.